Adopting the Fall Tailoring Interventions for Patient Safety (TIPS) Program to Engage Older Adults in Fall Prevention in a Nursing Home. Issue 4 (October 2021) - Tzeng, Huey-Ming; Jansen, Lynn S.; Okpalauwaekwe, Udoka; Khasnabish, Srijesa; Andreas, Brenda; Dykes, Patricia C.
Abstract : Background: Falls are the leading cause of injury-related hospitalizations and deaths among older adults globally. Local problem: About 24% of Canadian nursing home residents fall annually. This quality improvement project evaluated the impact of the Fall Tailoring Interventions for Patient Safety (TIPS) program on preventing falls and fall-related injuries among older adult nursing home residents in a subacute care unit in Canada. Methods: We used the Standards for Quality Improvement Reporting Excellence (SQUIRE) 2.0 guidelines for reporting. The intervention site is a 15-bed subacute care unit within a government-funded nursing home. Intervention: The Fall TIPS program was adapted to a nursing home setting to prevent falls. It provides fall prevention clinical decision support at the bedside. Results: The rates of falls and injuries decreased after implementing the Fall TIPS intervention. Conclusion: Engaging nursing home older adult residents in fall prevention is crucial in translating evidence-based fall prevention care into clinical practice. Abstract : Supplemental Digital Content is Available in the Text.